Optimalisasi Guru PPKn dalam Meningkatkan Minat Belajar Siswa Inklusi - Eneng Martini; Wulan Sari; Erry Hendriawan (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This research aims to optimize PPKn teachers in PPKn learning, increasing interest in learning for inclusive students, so that students can be independent in their interest in learning and teachers can achieve the expected results and can find out the obstacles faced by teachers in increasing interest in learning. This research has a problem formulation including: How is PPKn learning at SMA Muhammadiyah 1 Cimahi, what is the interest in learning of inclusive students in PPKn subjects at SMA Muhammadiyah 1 Cimahi, what obstacles do teachers face in increasing the interest in learning of inclusive students at SMA Muhammadiyah 1 Cimahi. This research uses a qualitative approach with descriptive research type. Data collection techniques in research are interviews, observation and documentation. The results of this research were to find out, increase interest in learning, and find obstacles in the context of PPKn learning at SMA Muhammadiyah 1 Cimahi, achieved by gaining a comprehensive understanding of the dynamics of learning and the challenges faced by teachers in creating an inclusive and motivating learning environment.